Predicting suitable timing for artificial reproductive technology treatment in aged infertile women. (29th March 2016) - Akino, Nana; Isono, Wataru; Wada‐Hiraike, Osamu
Abstract: It has been widely accepted that the age of women plays a fundamental role in fecundity, and age‐related fertility decline has one of the most significant and detrimental effects on the success rate of infertility treatment. Therefore, treatment cycles of non‐in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) treatment for infertile women of advanced aged have been limited due to their lack of efficacy, and they are often optimized, compared to IVF/ICSI treatment. Recent trends in infertility treatment apparently indicate that IVF/ICSI treatment, including egg donation, is frequently offered to aged women for first‐line management, despite its heavy burden, but hasty IVF/ICSI treatment should be avoided, considering its socioeconomic problems. It is important to distinguish women who could conceive by non‐IVF/ICSI treatment, although the optimization of non‐IVF/ICSI treatment protocols remains poorly understood. This review focuses on extracting aged patients who have higher chance of conceiving with non‐IVF/ICSI treatment and providing necessary and sufficient infertility treatment. After initial evaluation for fertility, including tubal factor, male factor, the presence of endometriosis and/or adenomyosis, and ovarian reserve, the outcomes of fertility treatment can be predicted to some extent in aged infertile women.